2017
DOI: 10.1111/jfd.12675
|View full text |Cite
|
Sign up to set email alerts
|

Infectious pancreatic necrosis virus (IPNV) serotype Sp is prevalent in Turkish rainbow trout farms

Abstract: Infectious pancreatic necrosis virus (IPNV) is a common pathogen of rainbow trout (Oncorhynchus mykiss) in Turkey. We found that 455 of 1,676 sample pools tested were IPNV positive. Positive samples were found in all geographical regions where sampling was conducted. Sequence and phylogenetic analyses of VP2 from 30 isolates representing all regions showed that the viruses were highly similar in sequence and grouped within Genogroup 5 (serotype Sp-A2). No correlations between sequences, sampling sites or geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 52 publications
6
22
0
Order By: Relevance
“…In Mexico [102], IPNV isolates showed Thr at position 221 ( Figure 6L) which is indicative of persistence; however, although most isolates were from asymptomatic carriers-which confirms the predictions-one corresponded to an isolation from diseased rainbow trout. Something similar was reported in Chile [103], Turkey [104], and Taiwan [105], with isolates from clinical cases showing Thr at aa 221 . More recently, a discordance was also observed by Holopainen et al [80] in Finnish strains ( Figure 6P); they sequenced isolates obtained during a few decades and observed that all of them showed the aa Thr at position 221, in spite of the increasing virulence observed over recent years in Finish farms.…”
Section: Determinants Of Virulence In Vp2supporting
confidence: 78%
“…In Mexico [102], IPNV isolates showed Thr at position 221 ( Figure 6L) which is indicative of persistence; however, although most isolates were from asymptomatic carriers-which confirms the predictions-one corresponded to an isolation from diseased rainbow trout. Something similar was reported in Chile [103], Turkey [104], and Taiwan [105], with isolates from clinical cases showing Thr at aa 221 . More recently, a discordance was also observed by Holopainen et al [80] in Finnish strains ( Figure 6P); they sequenced isolates obtained during a few decades and observed that all of them showed the aa Thr at position 221, in spite of the increasing virulence observed over recent years in Finish farms.…”
Section: Determinants Of Virulence In Vp2supporting
confidence: 78%
“…() reported that these IPNV associated isolates are avirulent, so we could describe these species as dominant pathogens when present in a mixed infection with IPNV. Considering that IPNV is mostly isolated from rainbow trout with ascites (Büyükekiz et al., ), there is a question as to which agent is responsible for the ascites. A. salmonicida (A5) isolated from dorsal lesions of broodstock rainbow trout (3,000 g) was combined with Y. ruckeri and IPNV.…”
Section: Discussionmentioning
confidence: 90%
“…( E. cloacae, M. psychrotolerans and Flavobacterium articles in process). (Table ; Büyükekiz et al., ; Duman, Altun et al., ; Duman, Saticioglu et al., ; Duman, Buyukekiz et al., ). In some cases, only A. sobria, A. media, A. bestiarum and A. salmonicida isolates were seen as primary infectious agents in rainbow trout showing dorsal lesions and from water temperatures between 9.5 and 19.1°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations